126k views
5 votes
Explain to a new student how to simplify the expression below. Show the updated expression after each step you take.

(-8)+(-3)+(-4)(7) ÷14+9(-2)

1 Answer

6 votes

Answer:

-31

Explanation:

You use pemdas which is

parathesis

exponents

multiply or divide, use in order

then add or subtract, use in order

(-8)+(-3)+(-4)(7)÷14+9(-2)

multiply first

-4*7=-28

(-8)+(-3)+(-28)÷14+9(-2)

Divide next

-28÷14=-2

(-8)+(-3)+(-2)+9(-2)

multiply again

9*(-2)=-18

(-8)+(-3)+(-2)+(-18)

now add

-8+(-3)=-11

(-11)+(-2)+(-18)

add again

-11+(-2)=-13

(-13)+(-18)

add for the last time

-13+(-18)=-31

User Perigon
by
4.9k points